2015
DOI: 10.1021/acs.inorgchem.5b01048
|View full text |Cite
|
Sign up to set email alerts
|

Novel Two- and Three-Dimensional Organometallic–Organic Hybrid Materials Based on Polyphosphorus Complexes

Abstract: The reaction of the silver salt Ag[Al{OC(CF3)3}4] (1) with the P2 ligand complex [Cp2Mo2(CO)4(η2-P2)] (2) and the organic ditopic linker trans-1,2-di(pyridine-4-yl)ethene (dpe) results in the formation of four novel organometallic–organic hybrid compounds. Depending on the reaction conditions, the two-dimensional networks [{Cp2Mo2(CO)4(μ4,η1:1:2:2-P2)}(μ,η1:1-C12H10N2)Ag]n[Al{OC(CF3)3}4]n·0.075nCH2Cl2·1.425nC6H6 (3) and [{Cp2Mo2(CO)4(μ3,η2:2:2-P2)}2(μ,η1:1-C12H10N2)3Ag2]n[Al{OC(CF3)3}4]2n·2nC7H8 (4) are access… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 34 publications
(4 citation statements)
references
References 44 publications
(59 reference statements)
0
4
0
Order By: Relevance
“…Phosphorus containing polymers have been of growing interest in a variety of applications such as dental adhesives, [37] flame retardants [38,39], and ligands in various organic–inorganic frameworks and hybrid materials [40]. Synthesis of phosphorus-containing monomers and block copolymers thereof are of growing interest in fields of biomedicine, ref.…”
Section: Introductionmentioning
confidence: 99%
“…Phosphorus containing polymers have been of growing interest in a variety of applications such as dental adhesives, [37] flame retardants [38,39], and ligands in various organic–inorganic frameworks and hybrid materials [40]. Synthesis of phosphorus-containing monomers and block copolymers thereof are of growing interest in fields of biomedicine, ref.…”
Section: Introductionmentioning
confidence: 99%
“…P 2 complex A1 readily forms homoleptic dinuclear complexes [M 2 ( A1 ) 4 ] 2+ with monovalent cations M + (M = Cu, Ag, Au), and these exhibit dynamic coordination behavior in solution . Addition of organic linker molecules to solutions of these complexes gives access to heteroleptic organometallic–organic hybrid materials, forming polymers, extended frameworks, or isolated rectangles . Additionally, it was demonstrated that introduction of A1 to di- and trinuclear Cu I complexes containing bridging mixed P,N ligands or polyphosphine ligands affords original coordination modes for A1 without the collapse of the preassembled multimetallic fragments .…”
Section: Introductionmentioning
confidence: 99%
“…The Ag–P bonds [2.5795(8)–2.6040(8) Å] are slightly elongated compared to those of similar hybrid polymers previously reported. [6a] The Ag ··· Ag distance is long (5.480 Å) revealing no argentophilic interactions . The Ag 2 P 4 six‐membered motifs in 4 are nearly planar (folding angle 0.04°).…”
Section: Resultsmentioning
confidence: 99%
“…This novel approach succeeded in the synthesis of novel “organometallic‐organic” hybrid polymers [where P n ‐based organometallic fragments (nodes) are linked by organic spacers], which could not be obtained from classical two‐component reactions. For example, the tetrahedrane complex [Cp 2 Mo 2 (CO) 4 (η 2 ‐P 2 )] (Cp = C 5 H 5 ) ( 1 ) was treated with Ag I or Cu I salts in the presence of dipyridylethene to yield unprecedented one‐, two‐, and three‐dimensional “organometallic‐organic” coordination polymers . These results motivated us to expand our research field raising the question as to whether it is possible to utilize some other N donor ligands in our reactions.…”
Section: Introductionmentioning
confidence: 99%